2022
DOI: 10.3390/nu14142822
|View full text |Cite
|
Sign up to set email alerts
|

Meeting 24-Hour Movement and Dietary Guidelines: Prevalence, Correlates and Association with Weight Status among Children and Adolescents: A National Cross-Sectional Study in China

Abstract: China is confronted with a “double burden” of underweight and overweight/obesity in children and adolescents. This study aimed to investigate the prevalence and correlates of meeting 24 h movement and dietary guidelines among Chinese children and adolescents. Further, the study aimed to examine the association of meeting 24 h movement and dietary guidelines in children and adolescents. A total of 34,887 Chinese children and adolescents were involved. Only 2.1% of participants met the 24 h movement guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…Regarding obesity‐related indicators, the most common obesity‐related indicators were zBMI [35, 37, 38, 40, 42, 44–47, 49, 55, 56], waist circumference [36, 38, 45, 48, 53, 54, 60], BMI [35, 36, 39, 41, 48, 53, 58], body fat by bioelectrical impedance analysis [57, 62] or dual‐energy x‐ray absorptiometry [38, 55], only obesity [48, 63], and overweight/obesity [35, 37, 41, 43, 46, 50–52, 56, 59, 61–63]. Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding obesity‐related indicators, the most common obesity‐related indicators were zBMI [35, 37, 38, 40, 42, 44–47, 49, 55, 56], waist circumference [36, 38, 45, 48, 53, 54, 60], BMI [35, 36, 39, 41, 48, 53, 58], body fat by bioelectrical impedance analysis [57, 62] or dual‐energy x‐ray absorptiometry [38, 55], only obesity [48, 63], and overweight/obesity [35, 37, 41, 43, 46, 50–52, 56, 59, 61–63]. Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63]. Sleep duration was determined by accelerometer‐based measures in 9 studies and self‐reported measures by young people and parents in 20 studies [35, 36, 40, 42–45, 47–53, 57, 59–63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PA, ST and sleep were measured using reliable and valid items derived from the Health Behavior in School-aged Children survey questionnaire which had been widely applied in previous studies with Chinese primary children (Cronbach’s alpha = 0.66–0.83) [ 2 , 37 , 38 , 39 ]. For PA, participants were asked to report “how many days they engaged in light physical activity at least 60 min on weekdays during the past week” and “how many days they engaged in moderate and vigorous physical activity (MVPA) at least 60 min on weekdays during the past week”.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy 24‐h movement behaviors (including physical activity [PA], sedentary behavior [SB], and sleep) are related to a variety of health benefits in children and adolescents. For example, movement behaviors at the recommended level have been found to be associated with various health outcomes (Saunders et al., 2016; Rollo et al., 2020), such as healthy weight management (Chen et al., 2021; García‐Hermoso et al., 2023; Roman‐Viñas et al., 2016), enhanced physical fitness (Chen et al., 2022; Tapia‐Serrano et al., 2023), reduced risks of depressive symptoms and anxiety (Liang et al., 2023; Sampasa‐Kanyinga et al., 2020), as well as healthful dietary patterns (Thivel et al., 2019; Yang et al., 2022). Such evidence supports the promotion of desired 24‐h movement behaviors on healthy growth and development in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%